COVID-19 status and its prevention among Indonesian adults - Nurhayati, Nurhayati; Dewi Setyawati, Asih (The Journal of Palembang Nursing Studies, 2022)
Background: The world has now impacted by COVID-19. Indonesia is one of the countries predicted to be affected over a longer period. The rapidly screening of COVID-19 status among Indonesians is important to prevent the massive spread of COVID-19. Purpose: The study aimed to investigate the covid status, and its prevention among Indonesians. Methods: A cross-sectional study was performed among Indonesians using a web-based survey that was randomly distributed using social media after a year of the outbreak of COVID-19 in Indonesia. There were 247 respondents enrolled this study. An emerging COVID-19 tool was utilised for data collection. Descriptive statistics and linear regression were applied with the significance value of 0.05. Results: From a total of 247 participants, 89 respondents had a travel history to the red zone area of COVID-19. 33% of them felt good but isolating after COVID-19 exposure. Most of them used facemasks (50.2%) and washing hands (36%) as health prevention during the COVID-19 outbreak. Conclusions: Identification of Covid status is important to prevent COVID-19 exposure.